The Application of Survival Analysis to Evaluating the Efficiency of a Professional Effectiveness Enhancement Programme - Markowicz, Iwona; Bieszk-Stolorz, Beata (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
The purpose of the paper is to evaluate the effect of a professional effectiveness enhancing programme on unemployment spells.The analysedprogramme was implemented by the PoviatLabour Office in Szczecin in 2010 and was targeted at under 30 year-olds. The survival analysis methods are going to be the starting point for the study. The differences in unemployment spells will be examined by means of the regression discontinuity model. The parameter values of this model will help evaluate the efficiency of the programme financed by the Labour Fund. The analysis will be based on the data of people de-registered from thePoviatLabour Office in Szczecin in 2010. The control group will consist of people de-registered in 2008, i.e. the year when the project was not realised.